A Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE): XV. The Hα luminosity function of the Virgo cluster - Boselli, Alessandro; Fossati, M.; Côté, P.; Cuillandre, J. C.; Ferrarese, L.; Gwyn, S.; Amram, P.; Ayromlou, Mohammadreza; Balogh, M.; Bellusci, G.; Boquien, M.; Gavazzi, G.; et al. (Astronomy and astrophysics, 2023)
We use a complete set of deep narrow-band imaging data for 384 galaxies gathered during the Virgo Environmental Survey Tracing Ionised Gas Emission (VESTIGE) to derive the first Hα luminosity function of the Virgo cluster within its virial radius. The data, which are sensitive to the emission of a single O-early B ionising star, allow us to cover the whole dynamic range of the Hα luminosity function (1036 ≤ L(Hα)≤1042 erg s−1). ...